Effects of elevated temperature and water-deficit stress on the potato aphid Macrosiphum euphorbiae (Thomas) (Hemiptera : Aphididae) and its parasitoid Aphidius ervi Haliday (Hymenoptera : Braconidae) - Kruger, Kerstin (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2016.